STRATEGI KOMUNIKASI DALAM MENINGKATKAN DAYA SAING KELEMBAGAAN USAHATANI PADI SAWAH DI KABUPATEN BATANG HARI - Jamaluddin; Muchlis, Fuad; Kurniasih, Siti (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
Kumpeh Ulu subdistrict is one of the centers of rice production in Muaro Jambi district that follows the Upsus Pajale program. This research aims to (1) determine the effect of land area, seeds, fertilizers, pesticides and labor on the production of Upsus program and Non Upsus rice field in Kumpeh Ulu subdistrict (2) knowing the effect of Upsus Pajale on increasing rice production in the Kumpeh Ulu subdistrict. The research location was chosen intentionally (purposive) in the village of Pudak and Teluk Raya village. The number of samples was calculated by Slovin method and obtained as many as 76 farmers of paddy rice consisting of 38 program Upsus farmers and 38 non Upsus farmers. Selecting the sample was used by simple random sampling method. The analysis in this research used Cobb-Douglas analysis and Chow test